Amido poroso como dispositivo de amorfização de carvedilol - Oliveira, Israel de França de (2022)
Carvedilol is a Class II drug, according to the Biopharmaceutical Classification System (BCS), with low solubility and high permeability. One way to circumvent this condition is to obtain an amorphous material, the problem for such material is its instability. In this sense, amorphization of Active Pharmaceutical Ingredients (APIs) in porous adsorbent systems is very promising, since molecular interactions between the new solid form of the drug and the adsorbent systems can prevent its recrystallization. Therefore, we sought to develop a system for amorphizing Carvedilol based on porous starch matrices. The starch hydrogel was produced by incorporating water under heating and constant stirring, then the water was gradually replaced by ethanol from the system and finally the ethanol was removed by rotary evaporation. In this way, the pores of the starch were formed. The incorporation of the API was carried out by the method of loading by solvent evaporation and physical mixing, in proportions of 1:1, 2:1 and 3:1. The samples were submitted to Fourier transform infrared (FTIR), thermogravimetric (TGA), differential scanning calorimetry (DSC) and X-ray diffraction analysis. In the Thermogravimetric results for the system with solvent incorporation, there was a significant change in the behavior of the thermal transition referring to melting, so that, in the 3:1 ratio, the melting peak disappears. Infrared spectra corroborate the presence of the drug within the polymer matrix. Such statement can be confirmed by the characteristic band of the carvedilol drug at 1592 cm-1. XRD revealed that for the macerated system there was no adequate incorporation of the API to the matrix, but for the system with solvent incorporation, the Bragg peaks of the drug disappeared as the proportion of the porous matrix increased. Thus, it is possible to affirm that ASP is an excellent strategy for the amorphization of Carvedilol.